Optimising Nutrition to Alleviate Age-Associated Functional Decline - Kostka, Tomasz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Appropriate nutrition is a cornerstone of preventive gerontology. This Special Issue of Nutrients provides new insights on nutritional assessment and potential modifications of nutritional behaviours and supplements to prevent age-associated disorders and to increase life expectancy in different populations of older subjects. It includes five original articles and four systematic reviews. This Special Issue presents several aspects of the assessment of nutritional status and the prevention and treatment of nutritional deficiencies in different populations of older adults. Undoubtedly, future research will deepen our knowledge on this crucial public health issue.